USE OF A ROOTING AGENT IN THE VEGETATIVE PROPAGATION OF BANANA (Musa paradisiaca L.) HARTON CLONE UNDER THERMAL CHAMBER CONDITIONS - SALVADOR-CARHUARUPAY, Markyori Sofí (2021)
The objective of this work was to determine the effect of different doses of the rooting agent Root-Hor® in the multiplication of suckers of the Harton clone (bellaco plantain) under thermal chamber conditions in the province of Padre Abad, Aguaytía, Peru. A thermal chamber 3m wide x 5m long and 1.8m high was built and lined with transparent plastic. In the rooting beds, compost was used as a base to form a layer 10cm deep, followed by phosphate rock sprinkled all over the bed and finally a 40cm layer of sawdust was added.Corms of healthy mother plants with an average weight of 2kg were selected, from which the central growth point was eliminated by making a cone cut 4cm deep in each corm. These were disinfected with a solution of 5% sodium hypochlorite for 3 minutes and then treated with the Root-Hor® rooting agent according to the doses studied (0ml/100L, 50ml/100L, 100ml/100L, 150ml/100L and 200ml/100L). Finally, they were placed in the rooting beds inside the thermal chamber, showing that the application of 150ml/100L of Root-Hor® achieved 8.2 suckers/corm, 330.4 g of weight/suckling, 118.2 cm of sucker height, 4 cm diameter of sucker, 20.4 roots/sucker and 25cm of root length, surpassing the other applications of Root-Hor® and the control,showing efficiency in the vegetative propagation of the Harton clone under thermal chamber conditions.